Assessment of the Left Ventricle Wall Motion Using Tagged Magnetic Resonance Imaging Data (tMRI) - Alenezy, Mohammed D. (Scientific Research, 2015)
In this paper, the Radial Strain (RS) and Strain Rate (SR) was calculated using tagged MRI (tMRI) data. Using tagged magnetic resonance imaging (tMRI), the left ventricle short axis of five healthy adults (three men and two women) and four healthy male rats was imaged during diastolic and systolic phases on the mid-ventricle level. The RS and radial SR of the left ventricle were calculated at the mid-ventricular level of the cardiac cycle. The peak RS for rat and human heart was found to be 46.8 ± 0.68 and 40.7 ± 1.44, respectively, and it occurred at 40% of the cardiac cycle for both human and rat hearts. The peak systolic and diastolic radial SR for human heart was 1.10 ± 0.08 s−1 and −1.78 ± 0.02 s−1, respectively, while it was 4.25 ± 0.02 s−1 and −5.16 ± 0.23 s−1, respectively for rat heart. The results show that tMRI data can be used to characterize the cardiac function during systolic and diastolic phases of the cardiac cycle, and as a result, it can be used to evaluate the cardiac motion by calculating its RS and radial SR at different locations of the cardiac wall during both diastolic and systolic phases. This study also approves the validity of the tagged MRI data to accurately describe the radial cardiac motion
Keywords: Left Ventricle; Radial Strain; Radial Strain Rate; Tagged MRI